Modification of magnetic properties and morphology of iron oxide particles of natural sand from Rokan River through copper doping and preparation using ball milling method - Gultom, Elika; Sinuraya, Salomo; Amiruddin, Erwin; Awitdrus, Awitdrus (Universitas Riau, 2025)
The magnetic susceptibility, magnetic properties, morphological properties, and composition of iron oxide nanoparticles of the natural sand in Rokan River, Rokan Hulu Regency, doped copper and prepared by the ball milling method. Processing of the magnetic and non-magnetic particle separation was carried out using iron sand separator (ISS). The ball milling process is ground in two stages for 70 hours and 30 hours and is divided into 3 parts and doped copper with concentrations (weight%) 0 wt%, 5 wt%, and 10 wt%, called BM2A, BM2B, and BM2C products. The calculation of the magnetic susceptibility of the sample is carried out based on the values (BT) and (B0). The resulting magnetic susceptibility decreases as the percentage of copper doping increases. Vibrating sample magnetometer (VSM) shows the magnetic properties of iron oxide particles produced, namely magnetization saturation (MS) decreases, coercivity value (HC) and loop squareness (Mr/MS) grow up, and remanent magnetization (Mr) and loop area (A) varies as doping concentration increases. Morphological properties and composition of iron oxide particles using a scanning electron microscope with energy dispersive X-ray (SEM-EDX). The average measurement of particles produced decreased with the increase in copper doping given, that is 121.960 ± 47.493 nm, 119.730 ± 37.03 nm, and 84.244 ± 34.392 nm. Copper element increased with the increase in doping concentrations given which were 0.76%, 7.11%, and 8.13%, while elements O, Si, and Fe decreased.